Organizing Cyber Justice for Children within Indonesia’s Juvenile Justice System - Grendy Gildan; Hanuring Ayu Ardhani Putri; Femmy Silaswaty (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2026)
The rapid advancement of digital technology has increased children’s involvement in cybercrime as both victims and offenders, creating challenges for Indonesia’s juvenile justice system. This study examines the legal framework governing juvenile cybercrime, evaluates law enforcement practices at the Surakarta District Court, and proposes an adaptive child-centered justice model. Using an empirical legal method with a socio-legal approach, the research analyzes legislation, court decisions, documentary evidence, and semi-structured interviews with law enforcement officials. The findings reveal incomplete harmonization among the Electronic Information and Transactions (EIT) Law, the Juvenile Criminal Justice System Law, and the Child Protection Law, limiting the effective implementation of diversion and restorative justice. Persistent normative, institutional, technical, and sociological barriers further reduce enforcement effectiveness. The study concludes that regulatory harmonization, stronger institutional capacity, modern digital infrastructure, and an integrated child protection ecosystem are essential for an effective juvenile cyber justice system.